Application of 2k Full Factorial Design in Optimization of Solvent-Free Microwave Extraction of Ginger Essential Oil - Mumtaj Shah; S. K. Garg (Journal of Engineering)
The solvent-free microwave extraction of essential oil from ginger was optimized using a 23 full factorial design in terms of oil yield to determine the optimum extraction conditions. Sixteen experiments were carried out with three varying parameters, extraction time, microwave power, and type of sample for two levels of each. A first order regression equation best fits the experimental data. The predicted values calculated by the regression model were in good agreement with the experimental values. The results showed that the extraction time is the most prominent factor followed by microwave power level and sample type for extraction process. An average of 0.25% of ginger oil can be extracted using current setup. The optimum conditions for the ginger oil extraction using SFME were the extraction time 30 minutes, microwave power level 640 watts, and sample type, crushed sample. Solvent-free microwave extraction proves a green and promising technique for essential oil extraction.